Fracture toughness reinforcement by CNT on G/E/C hybrid composite. (2021) - Gnanavel, C.; Saravanan, R.; Gopalakrishnan, T.; Pugazhenthi, R.
Abstract: There is an enormous application that can be found in the incorporation of CNT for improving properties because of its unique and properties. It is believed that the incorporation of CNT with the hybrid composite moderately increases the strain energy release rate. Hence this piece of investigation focuses on the inclusion of the single wall CNT in Glass/epoxy/carbon hybrid composite. The epoxy used as a matrix phase and the Glass and Carbon woven fibbers used as the reinforcement phase. The mode 1 test employed to investigate the toughness of composites that fabricated with different fashions. In the matrix phase, Carbon Nano Tubes were mixed with epoxy resin in an effort to improve the fracture toughness and it varies from0 to 2 wt% of CNTs. The handy layup technique is used to fabricate the samples. The samples can be characterized by a double cantilever beam test. The result shows that the superior toughening performance of this composite. The toughness of the hybrid composite is enhanced because the extra energy is required to break the CNT for crack propagation in the matrix phase. It is also noted that increasing CNT beyond 1 wt% of CNT'scan be attributed to the slippage among CNT's. It leads to reduce the fracture toughness of the hybrid composite.